Analysis of T‐cell responses directed against the spike and/or membrane and/or nucleocapsid proteins in patients with chilblain‐like lesions during the COVID‐19 pandemic. (7th September 2021) - Cassius, C.; Merandet, M.; Frumholtz, L.; Bergerat, D.; Samri, A.; Grolleau, C.; Grzelak, L.; Schwartz, O.; Yatim, N.; Moghadam, P.; Jaume, L.; Bagot, M.; et al.
Abstract :